Utilization of Tarsia Puzzle in Improving Learning on Integers, Rationals, Patterns, And Algebra (Irpa) Among Senior High School Students in a Public School - A. Tadios, Christine (Journal of Higher Education and Academic Advancement, 2024)
The research was conducted in order to improve students’ mastery level of the pre-requisite skills in General Mathematics such as integer, rational, patterns and algebra. The teacher observed that students’ performance is greatly affected by their poor mastery of the pre-requisite skills. The research involves thirty student respondents who were purposively selected based on their score on the pre-test given to them at the beginning of the semester. Students were ranked based on the score they got in the pre-test. The bottom thirty were then selected as respondents of the study. The respondents were given Tarsia-aided remedial classes as intervention. Tarsia is a software that allows teachers to create a variety of puzzles like jigsaw and dominoes. Sixty-minute remedial classes of two to three session per week started on the month of September 2021. A blended learning modality was adapted. The researcher gathered data using the pre-test and post-test result of the respondent. It was found out that the average of the score of the thirty respondents in the 50-item pre-test is 8.13. The average of the scores of the students increased by 11.2 points during the post-test that was given after the intervention. Using t-test for paired samples, it was fund out that there is a significant difference between students’ pre-test and post-test scores. Thus, the Tarsia-aided remedial classes improved students’ mastery of the pre-requisite skills.